2021
DOI: 10.3390/w13182503
|View full text |Cite
|
Sign up to set email alerts
|

Key SARS-CoV-2 Mutations of Alpha, Gamma, and Eta Variants Detected in Urban Wastewaters in Italy by Long-Read Amplicon Sequencing Based on Nanopore Technology

Abstract: The emergence of SARS-CoV-2 variants of concern (VOCs) and variants of interest (VOIs) poses an increased risk to global public health and underlines the need to prioritise monitoring and research to better respond to the COVID-19 pandemic. Wastewater monitoring can be used to monitor SARS-CoV-2 spread and to track SARS-CoV-2 variants. A long read amplicon sequencing approach based on the Oxford Nanopore technology, targeting the spike protein, was applied to detect SARS-CoV-2 variants in sewage samples collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Today, we know that human pathogens in wastewater can represent a good proxy of the concentrations excreted by the population afferent to the treatment plant if they persist long enough (2–4 days) to be detected ( Brouwer et al, 2018 ; Carducci et al, 2020 ; Kitajima et al, 2020 ). Therefore, monitoring temporal changes in viral concentrations and diversity in community wastewater samples can be used not only to determine the true extent of the infection in the population but also the emergence of new viral strains and the early detection of new viral outbreaks ( Ahmed et al, 2020 ; Daughton, 2012 ; Johnson et al, 2021 ; Hart and Halden, 2020 ; La Rosa et al, 2021b ; Monteiro et al, 2022 ). While retrospective studies have already demonstrated the feasibility as an alert system, WBE for real-time early warning cannot be realized without frequent sampling, rapid sample delivery, analytical turnaround, and reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Today, we know that human pathogens in wastewater can represent a good proxy of the concentrations excreted by the population afferent to the treatment plant if they persist long enough (2–4 days) to be detected ( Brouwer et al, 2018 ; Carducci et al, 2020 ; Kitajima et al, 2020 ). Therefore, monitoring temporal changes in viral concentrations and diversity in community wastewater samples can be used not only to determine the true extent of the infection in the population but also the emergence of new viral strains and the early detection of new viral outbreaks ( Ahmed et al, 2020 ; Daughton, 2012 ; Johnson et al, 2021 ; Hart and Halden, 2020 ; La Rosa et al, 2021b ; Monteiro et al, 2022 ). While retrospective studies have already demonstrated the feasibility as an alert system, WBE for real-time early warning cannot be realized without frequent sampling, rapid sample delivery, analytical turnaround, and reporting.…”
Section: Discussionmentioning
confidence: 99%
“…With accurate diagnosis, prompt isolation of patients, and early treatment, the SARS 2003 outbreak ended in June with 8098 reported cases and 774 deaths worldwide [38] without a variant of concern reported. It is of interest to note that the CDC developed a sequencing-based molecular test to facilitate ending the SARS epidemic so quickly by using just 15 positive SARS patient samples for method development and that a method for the determination of SARS-CoV-2 variants in sewage was developed by nested RT-PCR amplification of the S gene in only six samples, followed by conventional Sanger sequencing of the cDNA PCR amplicons [39]. The method presented in this article followed the CDC's established SARS 2003 protocols [35][36][37] to sequence two ~400-base segments of the S gene of SARS-CoV-2 for accurate determination of SNP and indel mutations, which are used to determine amino acid changes to further define variants.…”
Section: Discussionmentioning
confidence: 99%
“…Massive parallel sequencing techniques applied to sewage samples allow us to analyze a large number of SARS-CoV-2 genomes, including those present in symptomatic and asymptomatic persons. Through the analysis of sequences, it is possible to detect low-frequency variants (LFV) and to infer which lineages are circulating at a certain time and place ( Bar-Or et al, 2021 ; Crits-Christoph et al, 2021 ; Dharmadhikari et al, 2021 ; Herold et al, 2021 ; Izquierdo-Lara et al, 2021 ; La Rosa et al, 2021 ; Nemudryi et al, 2020 ; Rios et al, 2021 ). Additionally, genomic analyses may allow to detect the entry of described lineages or Variants of Concern (VOCs) into populations, as well as the appearance of emerging lineages, to characterize new outbreaks, and to aid in viral strains tracking ( Bar-Or et al, 2021 ; Crits-Christoph et al, 2021 ; Izquierdo-Lara et al, 2021 ; La Rosa et al, 2021 ; Nemudryi et al, 2020 ; Rios et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Through the analysis of sequences, it is possible to detect low-frequency variants (LFV) and to infer which lineages are circulating at a certain time and place ( Bar-Or et al, 2021 ; Crits-Christoph et al, 2021 ; Dharmadhikari et al, 2021 ; Herold et al, 2021 ; Izquierdo-Lara et al, 2021 ; La Rosa et al, 2021 ; Nemudryi et al, 2020 ; Rios et al, 2021 ). Additionally, genomic analyses may allow to detect the entry of described lineages or Variants of Concern (VOCs) into populations, as well as the appearance of emerging lineages, to characterize new outbreaks, and to aid in viral strains tracking ( Bar-Or et al, 2021 ; Crits-Christoph et al, 2021 ; Izquierdo-Lara et al, 2021 ; La Rosa et al, 2021 ; Nemudryi et al, 2020 ; Rios et al, 2021 ). These studies also evidenced that improvement on sequencing techniques must be performed in order to reduce error rates, as the case of Nanopore sequencing ( Nemudryi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%